First principle investigation of electronic structure and optical behaviors of 2-amino-4-fluorododec-4-encarbolic acid. (March 2015) - Reshak, A.H.; Khan, Saleem Ayaz
Abstract: The electronic structure and dispersion of optical susceptibilities of 2-amino-4-fluorododec-4-encarbolic acid were calculated using all-electron full potential linear augmented plane wave method based on density functional theory. Perdew–Burke–Ernzerhof generalized gradient approximation (PBE-GGA) and Engel Vosko generalized gradient approximation (EV-GGA) were used to solve the exchange correlation functional. The EV-GGA scheme was selected to obtain better band gap value (4.91 eV) as compared to GGA-PBE (4.75 eV). The valence electron charge density plots show foremost covalent nature of the bonds. The C–C bond is pure covalent bond while C–H, C–F, C–O, N–H and C–N configuration show dominant covalent bond with small percentage of ionicity. The calculated spectral peaks in ε 2 ( ω ) show electron transition between the occupied and unoccupied bands. The calculated absorption coefficient I ( ω ) and reflectivity spectra R ( ω ) of 2-amino-4-fluorododec-4-encarbolic acid show response to electromagnetic radiation in extreme ultraviolet region (UV-C). The dispersion of calculated second order dielectric tensor components ε 2 ( ω ), ε 1 ( ω ), I ( ω ) and L ( ω ) show considerable anisotropy.